(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
The article addresses the use of masks and sculptures in the traditional folguedos (folk festivities) of the Southeast region, focusing on the Folia de Reis (Epiphany procession) and the Guarda de Congo (Congo Guard) of Espírito Santo (ES). In the first case, we discuss the mask in the Folia de Reis procession, both for the clowns or marungos, and for the Three Wise Men characters. In the second case, we discuss the percussive instrument called casaca. Typical of Espírito Santo, this reco-reco (scraper) with a doll’s head is specific to the congo bands, and has features that could be considered mamulengo figures (hand puppets), due to being made of wood and having comical features.